The effect of Phoenix dactylifera pollen on the expression of NRF2, SOD2, CAT, and GPX4 genes, and sperm parameters of fertile and infertile men: A controlled clinical trial - Soghra Fallahi; Minoo Rajaei; Mohammad Javad Hesam; Mohsen Koolivand; Kianoosh Malekzadeh (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Oxidative stress is caused by the imbalance occurring between the creation and clearance of the reactive oxygen species (ROS), which is responsible for 30-40% of male infertility. The positive impact of phoenix dactylifera pollen (Date palm pollen, DPP) on the improvement of sperm parameters has been well documented in animal models. Objective: For evaluating the effect(s) of DPP on sperm parameters, ROS levels, expression of antioxidant genes, and activity of antioxidant enzymes of infertile men. Materials and Methods: In this controlled clinical trial, a total of 60 male case with infertility and 20 normospermic fertile men were recruited. Before and after the treatment with DPP, the case were administered 400 mg/kg of gelatinous capsules daily for 30 consecutive days and semen samples were taken. Quantitative real-time polymerase chain reaction was applied for the evaluation of the mRNA expression levels of Nuclear factor erythroid 2-related factor 2(NRF2), superoxide dismutase (SOD2), glutathione peroxidase 4(GPX4), and catalase (CAT) genes. Results: The mRNA expression levels of NRF2, SOD2, GPX4, and CAT (p < 0.05 for all) and significantly increased after treatment with DPP. The increased expressions of all antioxidant genes and enzymes significantly correlated with improvement in semen parameters including count (p = 0.01), motility (p = 0.05), and morphology (p = 0.01) of sperm. A significant correlation between the alteration of SOD2 gene expression and SOD activity, GPX4 and GPX, and CAT were also observed (p = 0.05). Conclusion: DPP can increase the expressions of NRF2, GPX4, SOD2, and CAT genes and also improve the semen quality in infertile men.